2014
DOI: 10.1159/000365840
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Decreases Cerebral Arterial Pulsatility in Patients with Mild White Matter Hyperintensities: Subgroup Analysis from the Effect of Cilostazol in Acute Lacunar Infarction Based on Pulsatility Index of Transcranial Doppler (ECLIPse) Study

Abstract: Background: The Effect of Cilostazol in Acute Lacunar Infarction Based on Pulsatility Index of the Transcranial Doppler (ECLIPse) study showed a significant decrease in the transcranial Doppler (TCD) pulsatility index (PI) with cilostazol treatment at 90 days after acute lacunar infarction. The aim of the present study was to perform a subgroup analysis of the ECLIPse study in order to explore the effect of cilostazol in acute lacunar infarction based on cerebral white matter hyperintensities (WMH) volume. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…However, when estrus cycle was monitored for stroke surgery timing, there was no notable difference in vaginal swaps between control and diabetic rats. While several clinical studies suggested that diabetes increases E2 levels in postmenopausal women, data on premenopausal women is missing and it is possible that E2 is decreased in our model (Han et al, 2014). ERα in the hypothalamus has been shown to regulate energy expenditure and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 96%
“…However, when estrus cycle was monitored for stroke surgery timing, there was no notable difference in vaginal swaps between control and diabetic rats. While several clinical studies suggested that diabetes increases E2 levels in postmenopausal women, data on premenopausal women is missing and it is possible that E2 is decreased in our model (Han et al, 2014). ERα in the hypothalamus has been shown to regulate energy expenditure and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 96%
“…Cilostazol, one of the antiplatelet agents frequently used in stroke prevention, can lower PI in acute stroke by reducing vascular resistance in cerebral circulation through vasodilation. 5 32 High doses of statins may reduce PI by upregulation of endothelial nitric oxide synthase activity and downregulation of superoxide production. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol reportedly decreases cerebral arterial pulsatility in patients with mild WMH. 103 Alternatively, triflusal, a drug with an effect similar to that of aspirin but with fewer bleeding complications, 104 may also be used in patients with a bleeding tendency (e.g., multiple CMBs) SVD patients. Further studies are required to find the appropriate antiplatelets in patients with SVD.…”
Section: Treatment and Secondary Preventionmentioning
confidence: 99%